Parametric Simulation of Artificial Light Effects on Vertical Illuminance for Circadian Stimulus in Open-Plan Office - Galih Rizki Nursuryani; Agus Hariyadi (Universitas Muhammadiyah Surakarta, 2026)
Lighting contributes not only to visual performance but also to the regulation of human circadian rhythms. One of the key parameters in evaluating circadian-effective lighting is vertical illuminance at eye level, which represents the amount of light reaching the human eye. Based on circadian lighting principles, appropriate levels of vertical illuminance are required to support alertness and biological rhythm alignment during daytime. This study investigates the effects of interior surface reflectance and correlated color temperature (CCT) on vertical illuminance in an open-plan office environment. A parametric simulation was conducted using DIALux evo, based on a fixed layout of office space and luminaires. Two CCT conditions representing daytime lighting were applied: 6500 K (08:00–12:00) and 5000 K (12:00–16:00). Interior surface reflectance values for ceiling, walls, and floor were systematically varied to evaluate their impact. The simulation excludes daylight contribution to isolate the effects of artificial lighting parameters. The results show that the average vertical illuminance ranges from 381 lux to 571 lux across all scenarios. High-reflectance scenarios produce illuminance levels exceeding 500 lux, indicating strong circadian stimulation but potential overlighting conditions. In contrast, low-reflectance scenarios fall within the recommended range of 250–500 lux, providing more balanced circadian-effective lighting. These findings indicate that interior surface reflectance has a significant influence on vertical illuminance, while the effect of CCT is not significant under the studied conditions. Therefore, reflectance can be considered a critical design parameter in achieving circadian-supportive lighting environments in office spaces.